Daya Dukung Fungsi Lindung Wilayah Ibu Kota Nusantara (IKN) - Wicaksono, Maulana Malik; Widyandini, Arifa Marsanda; Choirunnisa; Salsabhila, Melvina Ardela; Fariz, Trida Ridho; Jabbar, Abdul; Haris, Amnan (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
Penajam Paser Utara and parts of Kutai Kartanegara, East Kalimantan regions were selected as the location of the relocation of the National Capital of Indonesia. Significant land use changes have occurred since 2000 until 2023 and potentially affect changes in the carrying capacity of the protected function from before and current development. This study aims to determine the carrying capacity of the protected function in the development area of the Nusantara Capital City (IKN). The study results show that the carrying capacity of the protected function in the Nusantara Capital City area in 2000 resulted in a value of 0.42 while in 2023 it resulted in a value of 0.50. Both values are in moderate condition where in 2000 it was dominated by shrubs while in 2023 it has an increase in land area in the form of plantation forests that dominate the Nusantara Capital City area and the expansion of agricultural land as well as settlements and other buildings. Keywords: Carrying Capacity of The Protected Function, Nusantara Capital City, Land-use Change